A hybrid SD–DES simulation approach to model construction projects. Issue 1 (5th January 2015) - Moradi, Saeed; Nasirzadeh, Farnad; Golkhoo, Farzaneh
Abstract : Purpose: – The purpose of this research is to propose a hybrid simulation framework which can take into account both the continuous and operational variables affecting the performance of construction projects. Design/methodology/approach: – System dynamics (SD) simulation paradigm is implemented for the modelling of the complex inter-related structure of continuous variables and discrete event simulation (DES) is implemented for the modelling of operational influencing factors. A hybrid modelling framework is then proposed through combination of SD and DES to simulate the construction projects. Findings: – This paper discusses the deficiencies of two traditional simulation methods – SD and DES – for simulation of construction projects which can be compensated by implementing hybrid SD–DES model. Different types of basic hybrid structures and synchronisation methods of SD and DES models are introduced. Practical implications: – The proposed hybrid framework discussed in this research will be beneficial to modellers to simulate construction projects. Originality/value: – The paper introduces a theoretical framework for a hybrid continuous- discrete simulation approach which can take into account the dynamics of project environment arising from the complex inter-related structure of various continuous influencing factors as well as the construction operations. Different steps required to develop the hybrid SD–DES model and synchronisation of SD and DES simulation methods are illustrated.